Advances in nutrition of the newborn infant. Issue 10079 (22nd April 2017) - Harding, Jane E; Cormack, Barbara E; Alexander, Tanith; Alsweiler, Jane M; Bloomfield, Frank H
Summary: Nutrition of newborn infants, particularly of those born preterm, has advanced substantially in recent years. Extremely preterm infants have high nutrient demands that are challenging to meet, such that growth faltering is common. Inadequate growth is associated with poor neurodevelopmental outcomes, and although improved early growth is associated with better cognitive outcomes, there might be a trade-off in terms of worse metabolic outcomes, although the contribution of early nutrition to these associations is not established. New developments include recommendations to increase protein supply, improve formulations of parenteral lipids, and provide mineral supplements while encouraging human milk feeding. However, high quality evidence of the risks and benefits of these developments is lacking. Clinical trials are also needed to assess the effect on preterm infants of experiencing the smell and taste of milk, to determine whether boys and girls should be fed differently, and to test effects of insulin and IGF-1 supplements on growth and developmental outcomes. Moderate-to-late preterm infants have neonatal nutritional challenges that are similar to those infants born at earlier gestations, but even less high quality evidence exists upon which to base clinical decisions. The focus of research in nutrition of infants born at term is largely directed at new formula products that will improve cognitive and metabolic outcomes. Providing the most effective nutrition to preterm infants should be prioritised as an important focus of neonatal care research to improve long-term metabolic and developmental outcomes.